A Qualitative Study on Religious Attributions Regarding Cancer - Kurt, Emine; Gurses, Ibrahim (Hitit Univ, 2024)
Cancer is a significant crisis that goes beyond being a global health issue marked by increasing incidence and mortality rates; it also encompasses psychosocial and spiritual dimensions. The existential and spiritual crises experienced by cancer patients are reflected in questions such as Why me?, Why did I get cancer?, and Why did God give this to me?. These inquiries reflect patients' attempts to find meaning in their cancer journey. The search for meaning involves understanding the reasons behind a crisis and its impact on their lives. One way to address meaning is through causal attributions. In the context of cancer, various known causal factors can be identified, including environmental influences, bad luck, stress, heredity, diet, or specific carcinogens. On the other hand, in both life-threatening diseases such as cancer and daily life, people often go beyond secular explanations, such as lifestyle and bad luck. Many people turn to religious attributions, including Allah's will, destiny, or divine wisdom to make sense of traumatic and overwhelming events in their lives. The search for meaning intensifies during distressing events such as disasters, death, and serious illnesses. Religion, as a comprehensive system of meaning, guides individuals in finding the answers they seek. Causal attributions affect the psychosocial well-being of cancer patients by shaping their sense of personal control. Referring to religious factors, such as Allah's will, can enhance hope and a sense of control when facing cancer. Interpreting a traumatic event as having a divine purpose and seeking wisdom in it can increase psychosocial adjustment. In contrast, negative spiritual evaluations, such as spiritual conflict and perceiving God as punishing, can hinder adjustment. Therefore, understanding the causal attributions related to cancer is crucial for managing the disease and treatment approaches. The aim of this research is to examine causal explanations, including religious attributions that have significant connections with various aspects and dimensions of cancer in Muslim Turkish cancer patients. A phenomenological approach, one of the qualitative research designs, was adopted to understand the experiences and meanings patients attribute to the phenomenon of cancer. Data were collected through interviews with 11 female patients diagnosed with breast cancer who were receiving outpatient treatment at Bursa Ali Osman Sonmez Oncology Hospital. The data were analyzed subjected to content analysis using the MAXQDA 20 program. The findings categorized causal explanations for cancer into non-religious attributions and religious attributions. Non-religious attributions were coded as stress and distress, heredity, smoking, and unhealthy diet. Among these, stress and distress was the most frequent code, while unhealthy diet was the least frequent. Religious attributions were coded as test, love, discipline, and destiny. Among these, test was the most frequent religious attribution, while destiny was the least frequent. The study found that patients tended to make more religious attributions for cancer compared to nonreligious ones, while also simultaneously referring to multiple factors (such as test and stress). This finding suggests that patients acknowledge both their own agency and Allah's authority in the causes of cancer. Another significant result was that religious attributions played a crucial role not only in making sense of and explaining cancer but also as a source of coping and spiritual growth. Patients who perceived cancer as a test from Allah or a result of being loved by Allah felt more valued and accepted the illness more readily. This result shows that positive religious attributions increase self-esteem in cancer patients. The findings obtained within the limitations of this research indicate that religious attributions are a significant subject requiring further investigation in broader sample groups including different types and stages of cancer. Furthermore, to effectively plan support interventions and models for oncology spiritual counseling, which is still in its early stages in our country, it is suggested to conduct research on the relationship and meditating role of religious attributions with various variables, such as psychosocial adjustment, coping, depression, and anxiety.
Kansere Yönelik Dinî Yüklemeler Üzerine Nitel Bir Araştırma
Keywords: Psychology of Religion; Cancer; Attribution Theory; Religious Attribution; Meaning